1997
DOI: 10.1038/sj.onc.1201367
|View full text |Cite
|
Sign up to set email alerts
|

The chimeric oncoproteins E2A-PBX1 and E2A-HLF are concentrated within spherical nuclear domains

Abstract: Oncogenic mutation of nuclear transcription factors often is associated with altered patterns of subcellular localization that may be of functional importance. The leukemogenic transcription factor gene E2A-PBX1 is created through fusion of the genes E2A and PBX1 as a result of t(1;19) in acute lymphoblastic leukemia. We evaluated subcellular localization patterns of E2A-PBX1 protein in transfected cells using immuno¯uorescence. Full-length E2A-PBX1 was exclusively nuclear and was concentrated in spherical dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Our subcellular localization studies show HPIP to be localized mainly in the cytoplasm, although a small amount was found in the nucleus. This finding, together with the knowledge that PBX is expressed in both nuclei and cytosol (48), implies that HPIP could in principle interact with PBX in either compartment. If the initial interaction occurs in the cytoplasm, the heterodimer would either stay in the cytosol or enter the nucleus as a complex.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our subcellular localization studies show HPIP to be localized mainly in the cytoplasm, although a small amount was found in the nucleus. This finding, together with the knowledge that PBX is expressed in both nuclei and cytosol (48), implies that HPIP could in principle interact with PBX in either compartment. If the initial interaction occurs in the cytoplasm, the heterodimer would either stay in the cytosol or enter the nucleus as a complex.…”
Section: Discussionmentioning
confidence: 87%
“…PBX, in contrast with E2A-PBX, is unable to activate transcription by itself (8,10,46); therefore, and based on our deletion data pointing at HPIP as a potential E2A-PBX binding protein, we studied the effect of HPIP on the ability of E2A-PBX to induce a luciferase reporter gene driven by seven copies of a E2A-PBX binding site (TGATTGAT) (47) upstream of the minimal FOS promoter. Co-expression of the E2A-PBX reporter plasmid, E2A-PBX, and HPIP decreased the E2A-PBX-mediated tran- 6 and 10 6 cells, respectively) stably expressing FLAG-HPIP were resolved on a 7.5% SDS-PAGE.…”
Section: The Sequence Of the Full Coding Region Of Hpip Revealed A Nomentioning
confidence: 99%
“…Two days after infection the coverslips were washed briefly in PBS, fixed for 10 min in 3.7% formaldehyde in PBS, and stored for various periods of time at 4°C immersed in 70% ethanol. Recombinant proteins were detected by indirect immunofluorescence using the YAE primary antibody at a 1:100 dilution and a fluorescein isothiocyanate-labeled secondary antibody (Jackson) at a 1:200 dilution according to a previously published protocol (32). Expression of the proteins E2A-GCN4 250-281 1-273 and VP16-NLS-Pbx1a was ascertained using monoclonal antibody clone G193-86 (Pharmingen, San Diego, Calif.) and a monoclonal antibody directed against the C terminus of Pbx1a (kindly provided by Michael Cleary, Stanford University), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The speckled hybridization pattern of Evi9a and Evi9b suggested that they are located within nuclear bodies or other subnuclear compartments (8,11,20,33). Many proteins are known to localize to these nuclear compartments.…”
Section: Evi9 Transcript Identificationmentioning
confidence: 99%